Comparative Performance of Microbial Desalination Cells Using Air Diffusion and Liquid Cathode Reactions: Study of the Salt Removal and Desalination Efficiency - Ramírez-Moreno, Marina; Rodenas, Pau; Aliaguilla, Martí; Bosch-Jimenez, Pau; Borràs, Eduard; Zamora, Patricia; Monsalvo, Víctor; Rogalla, Frank; Ortiz, Juan M.; Esteve-Núñez, Abraham (Frontiers in Energy Research, 2019)
Microbial Desalination Cell (MDC) represents an innovative technology which accomplishes simultaneous desalination and wastewater treatment without external energy input. MDC technology could be employed to provide freshwater with low-energy input, for example, in remote areas where organic wastes (i.e., urban or industrial) are available. In addition, MDC technology has been proposed as pre-treatment in conventional reverse osmosis plants, with the aim of saving energy and avoiding greenhouse gases related to conventional desalination processes. The use of oxygen reduction (i.e. O2 + 2H2O + 4e− → 4 OH−, E0′ = 0.815 V, pH = 7) was usually implemented as cathodic reaction in most of the MDCs reported in literature, whereas other strategies based on liquid catholytes have been also proposed, for example, ferro-ferricyanide redox couple (i.e. Fe(CN)63- + 1e− → Fe(CN)64-, E0 = 0.37 V). As the MDC designs in the literature and operation modes (i.e., batch, continuous, semi-continuous, etc.) are quite different, the available MDC studies are not directly comparable. For this reason, the main objective of this work was to have a proper comparison of two similar MDCs operating with two different catholyte strategies, and compare performance and desalination efficiencies. In this sense, this study compares the desalination performance of two laboratory-scale MDCs located in two different locations for brackish water and sea water using two different strategies. The first strategy consisted of an air cathode for efficient oxygen reduction, while the second strategy was based on a liquid catholyte with Fe3+/Fe2+ solution (i.e., ferro-ferricyanide complex). Both strategies achieved desalination efficiency above 90% for brackish water. Nominal desalination rates (NDR) were in the range of 0.17–0.14 L·m−2·h−1 for brackish and seawater with air diffusion cathode MDC, respectively, and 1.5–0.7 L·m−2·h−1 when using ferro-ferricyanide redox MDC. Organic matter present in wastewater was effectively removed at 0.9 and 1.1 kg COD·m−3·day−1 using the air diffusion cathode MDC for brackish and sea water, respectively, and 7.1 and 19.7 kg COD·m−3·day−1 with a ferro-ferricyanide redox MDC. Both approaches used a laboratory MDC prototype without any energy supply (excluding pumping energy). Pros and cons of both strategies are discussed for subsequent upscaling of MDC technology.